COMPREHENSIVE ANALYSIS OF HEALTH EQUITY IN PUBLIC HEALTH PRACTICE AND EXAMINING SOCIAL DETERMINANTS AND HEALTH DISPARITIES. - 1Abdullah Faris Mana Al Haydar, 2Marzoug Mubarak Gahes Al-Gahes, 3Norah Ali Hamed Alqahtani, 4Mahdi Mohammed Saeed Al yami, 5Ali Hussein Ali Alabbas, 6Saleh Hamad Hassan Al-theban, 7Hamad Rihan Mubarak AlQahes, 8Randa Saeed Samer Al-Saad, (Chelonian Research Foundation, 2022)
Health equity is a fundamental principle of public health practice aimed at achieving fair and just opportunities for everyone to attain their highest level of health. This article comprehensively audits the health equity in public health, focusing on social determinants and well-being. A comprehensive writing audit inspects different viewpoints of well-being equity, counting its definitions, determinants, measures, and impacts on well-being. Strategies for measuring well-being incongruities and procedures for progressing the well-being of people, communities, and frameworks are examined. Results and findings displayed in numbers, tables, and charts that outline the interaction between social determinants and well-being results. The need for mediation plans to kill well-being disparities and move forward well-being is emphasized. Whereas the discourse gives an understanding of the impacts of health equity on public health, well-being care, and well-being arrangement, the determination offers proposals for promoting health value in open health. Keywords: health equity, social determinants, health disparities, public health, population health, healthcare access.